2013
DOI: 10.1161/circulationaha.113.002627
|View full text |Cite
|
Sign up to set email alerts
|

Dispatcher-Assisted Cardiopulmonary Resuscitation

Abstract: Background-Dispatcher-assisted cardiopulmonary resuscitation (DA-CPR), in which 9-1-1 dispatchers provide CPR instructions over the telephone, has been shown to nearly double the rate of bystander CPR. We sought to identify factors that hampered the identification of cardiac arrest by 9-1-1 dispatchers and prevented or delayed the provision of dispatcher-assisted CPR chest compressions. Methods and Results-We reviewed dispatch recordings for 476 out-of-hospital cardiac arrests occurring between January 1, 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 27 publications
3
71
1
9
Order By: Relevance
“…The success of DACPR in getting bystander CPR started has not been well investigated. Recent studies showed that success rates are reported to be 40% and 50% 15, 16. Although the success rate of DACPR was less than 50% in this study, dispatcher instructions for CPR was effective for ongoing CPR (128/162 [79.0%]).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The success of DACPR in getting bystander CPR started has not been well investigated. Recent studies showed that success rates are reported to be 40% and 50% 15, 16. Although the success rate of DACPR was less than 50% in this study, dispatcher instructions for CPR was effective for ongoing CPR (128/162 [79.0%]).…”
Section: Discussioncontrasting
confidence: 50%
“…Dispatch‐assisted CPR is not a straightforward procedure and there can be many obstacles that prevent CPR instruction. Studies that reviewed the performance of DACPR have revealed that a certain proportion of CA cases were not eligible for CPR instruction because of callers’ refusal or physical factors 15, 16. In this current study, these were the major barriers to CPR instruction.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Since Carter et al 8. proposed that a CPR instruction to give five ventilations and chest compressions for 5 min should be given to a bystander by telephone in 1984, many reports have suggested that dispatchers are able to diagnose cardiac arrest over the telephone accurately, and dispatchers’ oral guidance may increase chest compressions by bystanders and improve patients’ outcomes 9, 10, 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Agonal breathing is common in the first few minutes following a cardiac arrest and, if correctly identified as a sign of cardiac arrest, is associated with higher survival rates. 1 Always be suspicious of cardiac arrest in a patient who presents with seizures: carefully check if the patient is breathing normally Immediately following cardiac arrest, because cerebral blood flow is reduced to almost zero, a short seizure-like episode may be witnessed that could be confused with epilepsy. Dental staff should be suspicious of cardiac arrest in any patient presenting with seizures.…”
Section: Guidelines 2015: Important Messagesmentioning
confidence: 99%